The Limits of Authoritarian Governance in Singapore's Developmental State
XXIII, 329 p. 3 illus.
Keywords: This book delves into the limitations of Singapore’s authoritarian governance model. In doing so, the relevance of the Singapore governance model for other industrialising economies is systematically examined. Research in this book examines the challenges for an integrated governance model that has proven durable over four to five decades. The editors argue that established socio-political and economic formulae are now facing unprecedented challenges. Structural pressures associated with Singapore’s particular locus within globalised capitalism have fostered heightened social and material inequalities, compounded by the ruling party’s ideological resistance to substantive redistribution. As ‘growth with equity’ becomes more elusive, the rationale for power by a ruling party dominated by technocratic elite and state institutions crafted and controlled by the ruling party and its bureaucratic allies is open to more critical scrutiny. Lily Zubaidah Rahim is an Associate Professor of Government & International Relations at the University of Sydney and a specialist in authoritarian governance, democratisation, ethnicity and political Islam. Her books include The Singapore Dilemma: The Political and Educational Marginality of the Malay Community, (1998) and Singapore in the Malay World: Building and Breaching Regional Bridges (2010), Muslim Secular Democracy (2013) and The Politics of Islamism (2018). Lily Zubaidah is currently President of the Malaysia and Singapore Society of Australia (MASSA) and Vice-President of the Australian Association of Islamic and Muslim Studies. Michael D. Barr is an Associate Professor of International Relations at Flinders University. His books include Lee Kuan Yew: The Beliefs behind the Man (2000), The Ruling Elite of Singapore (2014) and Singapore: A Modern History (2018). He was Editor-in-Chief of Asian Studies Review from 2012-2017. .